Pre-operative fasting in children: A guideline from the European Society of Anaesthesiology and Intensive Care. Issue 1 (January 2022) - Frykholm, Peter; Disma, Nicola; Andersson, Hanna; Beck, Christiane; Bouvet, Lionel; Cercueil, Eloise; Elliott, Elizabeth; Hofmann, Jan; Isserman, Rebecca; Klaucane, Anna; Kuhn, Fabian; de Queiroz Siqueira, Mathilde; et al.
Abstract : N/A: Current paediatric anaesthetic fasting guidelines have recommended conservative fasting regimes for many years and have not altered much in the last decades. Recent publications have employed more liberal fasting regimes with no evidence of increased aspiration or regurgitation rates. In this first solely paediatric European Society of Anaesthesiology and Intensive Care (ESAIC) pre-operative fasting guideline, we aim to present aggregated and evidence-based summary recommendations to assist clinicians, healthcare providers, patients and parents. We identified six main topics for the literature search: studies comparing liberal with conservative regimens; impact of food composition; impact of comorbidity; the use of gastric ultrasound as a clinical tool; validation of gastric ultrasound for gastric content and gastric emptying studies; and early postoperative feeding. The literature search was performed by a professional librarian in collaboration with the ESAIC task force. Recommendations for reducing clear fluid fasting to 1 h, reducing breast milk fasting to 3 h, and allowing early postoperative feeding were the main results, with GRADE 1C or 1B evidence. The available evidence suggests that gastric ultrasound may be useful for clinical decision-making, and that allowing a 'light breakfast' may be well tolerated if the intake is well controlled. More research is needed in these areas as well as evaluation of how specific patient or treatment-related factors influence gastric emptying. Abstract : Supplemental Digital Content is available in the text